The Secondary Purposes of Rhetorical Questions in the Holy Quran - محمود خورسندی; سمیه ترحمی; علیرضا خورسندی (مطالعات زبانی و بلاغی)
Questions are real if they are about what we do not know. But, sometimes they are used for purposes other than this primary purpose. In such cases, they are referred to as rhetorical questions. Rhetorical questions are one of the controversial issues in rhetoric. Some scholars think that this area belongs to semantics some think it falls in the same area as figures of speech. This article intends to explores different purposes of rhetorical Questions in the Holy Quran and provide Quranic examples to support the claims. There are two kinds of questions in the Quran: questions posed by God and Questions narrated from others. As God is omniscient and never seeks information, all these questions must be considered as rhetorical questions. Therefore, to better understand the secondary purposes of these questions, we have examined only questions which are posed by God to help the audience follow the right path.